A novel intellectual disability syndrome caused by GPI anchor deficiency due to homozygous mutations in PIGT. Issue 8 (1st May 2013) - Kvarnung, Malin; Nilsson, Daniel; Lindstrand, Anna; Korenke, G Christoph; Chiang, Samuel C C; Blennow, Elisabeth; Bergmann, Markus; Stödberg, Tommy; Mäkitie, Outi; Anderlid, Britt-Marie; Bryceson, Yenan T; Nordenskjöld, Magnus; et al.
Abstract : Purpose: To delineate the molecular basis for a novel autosomal recessive syndrome, characterised by distinct facial features, intellectual disability, hypotonia and seizures, in combination with abnormal skeletal, endocrine, and ophthalmologic findings. Methods: We examined four patients from a consanguineous kindred with a strikingly similar phenotype, by using whole exome sequencing (WES). Functional validation of the initial results were performed by flow cytometry determining surface expression of glycosylphosphatidylinositol (GPI) and GPI anchored proteins and, in addition, by in vivo assays on zebrafish embryos. Results: The results from WES identified a homozygous mutation, c.547A>C (p.Thr183Pro), in PIGT ; Sanger sequencing of additional family members confirmed segregation with the disease. PIGT encodes phosphatidylinositol-glycan biosynthesis class T (PIG-T) protein, which is a subunit of the transamidase complex that catalyses the attachment of proteins to GPI. By flow cytometry, we found that granulocytes from the patients had reduced levels of the GPI anchored protein CD16b, supporting pathogenicity of the mutation. Further functional in vivo validation via morpholino mediated knockdown of the PIGT ortholog in zebrafish ( pigt ) showed that, unlike human wild-type PIGT mRNA, the p.Thr183Pro encoding mRNA failed to rescue gastrulation defects induced by the suppression of pigt . Conclusions: We identified mutations in PIGT as the cause of a novel autosomal recessive intellectual disability syndrome. Our results demonstrate a new pathogenic mechanism in the GPI anchor pathway and expand the clinical spectrum of disorders belonging to the group of GPI anchor deficiencies.